Coupling effect on shallow slope stability under infiltration. Issue 5 (26th April 2019) - Zhang, Jian; Li, Jiangteng
Abstract : This paper aims to discuss the influence of the coupled deformation of unsaturated soil on slope stability under rainfall conditions. Numerical soil column tests were first performed to display seepage deformation and the pore water pressure (PWP) distribution differences of the coupled analysis. Comparative analyses were done for three different analysis cases (i.e. uncoupled analysis, coupled analysis without considering the permeability coefficient ( K s ) change and coupled analysis considering the K s change) under different infiltration intensities. The analysis results show that the coupled deformation leads to different PWP distributions and factor of safety profiles in the shallow slope from the uncoupled analysis, and the K s change caused by seepage deformation plays an important role. There is a great risk for accurately assessing the shallow slope state as to the uncoupled analysis and the coupled analysis without considering the K s change.